Flow in thin liquid film on an inclined solid surface - Hekmet Shareef Mustafa (College of Education for Pure Sciences, 2010)
Abstract : In this paper we concerned with two dimensional flow for incompressible thin liquid film on a solid surface which is inclined by an inclination angle  under the action of gravity force. We apply the momentum equations (Navier- Stokes) and the conservation of mass equation (continuity equation) with specified boundary conditions to obtain to equation that governs such flow, we use the numerical methods to find the thickness of the thin film.